Strategies to Dissect Host-Microbial Immune Interactions That Determine Mucosal Homeostasis vs. Intestinal Inflammation in Gnotobiotic Mice - Rogala, Allison R.; Oka, Akihiko; Sartor, R. Balfour (Frontiers in Immunology, 2020)
When identifying the key immunologic-microbial interactions leading to either mucosal homeostasis in normal hosts or intestinal inflammatory responses in genetically susceptible individuals, it is important not only to identify microbial community correlations but also to define the functional pathways involved. Gnotobiotic rodents are a very effective tool for this purpose as they provide a highly controlled environment in which to identify the function of complex intestinal microbiota, their individual components, and metabolic products. Herein we review specific strategies using gnotobiotic mice to functionally evaluate the role of various intestinal microbiota in host responses. These studies include basic comparisons between host responses in germ-free (GF), specific-pathogen-free or conventionally raised wild-type mice or those with underlying genetic susceptibilities to intestinal inflammation. We also discuss what can be learned from studies in which GF mice are colonized with single wild-type or genetically-modified microbial isolates to examine the functions of individual bacteria and their targeted bacterial genes, or colonized by multiple defined isolates to determine interactions between members of defined consortia. Additionally, we discuss studies to identify functions of complex microbial communities from healthy or diseased human or murine hosts via fecal transplant into GF mice. Finally, we conclude by suggesting ways to improve studies of immune-microbial interactions using gnotobiotic mice.